Hearing Status in Young People Using Portable Audio Players - PAWLACZYK-ŁUSZCZYŃSKA, Małgorzata; ZABOROWSKI, Kamil; ZAMOJSKA-DANISZEWSKA, Małgorzata; RUTKOWSKA-KACZMAREK, Paulina; DUDAREWICZ, Adam; ŚLIWINSKA-KOWALSKA, Mariola (Archives of Acoustics, 2017)
The aim of this study was to evaluate the hearing status in young adults using portable audio players (PAPs) in relation to their listening habits.The study included 58 subjects, aged 22.8±2.8 years, non-occupationally exposed to noise. Questionnaire inquiry aimed at collecting personal data, the information on PAPs usage habits, self-assessment of hearing status and identification of risk factors for noise-induced hearing loss (NIHL) were performedin study subjects. Hearing tests included pure-tone audiometry (PTA) and transient-evoked otoacoustic emission (TEOAE).All subjects were PAPs users. Depending on listening habits they were divided into the subgroups of “frequent” users (>1 h/day) and “non-frequent” users (1 h/day). There were no significant differences between subgroups in prevalence of NIHL risk factors and self-assessment of hearing status. However,frequent users more often complained of tinnitus and hyperacusis.Majority (81.9%) of participants had normal hearing. Nevertheless, 6.9% of audiograms showed high-frequency notches typical for NIHL. Both, the PTA and TEOAE indicated worse hearing in non-frequent users compared to frequent users. No significant differences in prevalence of high-frequency notches be-tween subgroups were noted.The outcomes do not support some previous studies results that the excessive exposure to music listened through PAPs might result in accelerating of development of NIHL loss in young adults.